2015
DOI: 10.1371/journal.pone.0140347
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Utility of a Data-Driven Approach for Assessing BMI from Face Images

Abstract: Several lines of evidence suggest that facial cues of adiposity may be important for human social interaction. However, tests for quantifiable cues of body mass index (BMI) in the face have examined only a small number of facial proportions and these proportions were found to have relatively low predictive power. Here we employed a data-driven approach in which statistical models were built using principal components (PCs) derived from objectively defined shape and color characteristics in face images. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Using different regression methods based on cross-validated sets of PCs, Wolffhechel et al [15] were able to account for 23% of BMI variation by facial shape, which is in the range of our results. Strikingly, they found that facial texture predicts 27% of variation in BMI, while we could predict only about 3% after cross-validation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Using different regression methods based on cross-validated sets of PCs, Wolffhechel et al [15] were able to account for 23% of BMI variation by facial shape, which is in the range of our results. Strikingly, they found that facial texture predicts 27% of variation in BMI, while we could predict only about 3% after cross-validation.…”
Section: Discussionsupporting
confidence: 78%
“…Wolffhechel and colleagues [15] predicted BMI by face shape and texture using more conventional multiple regression approaches. As they require substantially more cases than variables, we performed the regressions using smaller numbers of PCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These three measures do not necessarily capture all aspects of face shape that relate to weight perceived from faces. It is also possible to use an empirical approach to derive more global measures of facial shape that characterize facial adiposity using principal component analysis (PCA) of landmarks capturing the structure of two-dimensional (2D) facial images [32] or the entire surface of three-dimensional (3D) faces [33]. It remains to be shown how such measures relate to perceived health and measured health.…”
Section: (C) Facial Adipositymentioning
confidence: 99%